ENHANCING THE COMPETITIVENESS OF LOCAL COFFEE THROUGH INNOVATION IN PROCESSING, BRANDING, AND MARKETING IN GENGGELANG VILLAGE, NORTH LOMBOK - Kynaya, Erlangga Masykur; Ivo Yekti Nadirah; Khansa Saifany Zuhri; Marina Kurniasari; Dimas Ahmad Al Hakami; Nabila Alya Azzahra; Lalu Haikal Pasha Ahmad; Zaenab Nur Azkiai; Zidan Fahmi Az Zahir; Muhammad Rafif Fajriatmaja (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Genggelang Village in North Lombok Regency, West Nusa Tenggara, holds significant potential as a coffee-producing region, with over 50% of its land dedicated to coffee farming. However, most farmers continue to sell unprocessed green beans, missing the opportunity to increase value through post-harvest processing, branding, and market access. This community service initiative, carried out under the KKN Universitas Sebelas Maret (UNS) program, aimed to enhance local awareness and capacity in coffee innovation. Socialization activities were conducted directly in the village’s residential centers to ensure accessibility and participation. Findings revealed that farmers face cognitive and systemic barriers, including limited knowledge of fermentation, roasting, and marketing strategies. Many were unaware of the potential income boost from processing and branding. However, the involvement of local practitioners (a café owner and a coffee exporter) and the interactive format encouraged high engagement and motivation. Participants expressed a willingness to collaborate on product development and marketing, signaling a positive shift toward self-sufficiency. This initiative demonstrates that targeted, community-based outreach can uncover and address key developmental gaps, laying the groundwork for a sustainable local coffee industry.